Structural reliability analysis by the finite element method - Tan, Mingliu (2018)
In structural design, the uncertainties in load, materials and environment cannot be avoided and it is a naturally inherent phenomenon. To reduce or minimize the uncertainties in the structure, deterministic design and reliability-based design can be used to analysis the structure. For the simple structures, deterministic design method is used and the uncertainties can be represented by a safety factor. However, deterministic design method is a coarse approximation in structural design, it is not suitable for complex structural analysis and it may cause design failure and increase the design cost. Hence, structural reliability-based design method was introduced and it is more reliable than deterministic design approach. Structural reliability-based analysis is also called as structural probability analysis. Reliability design provide a more efficient way to evaluate the failure probability of the complex structures. The designers and engineer could predict the probabilistic design in early stage and reduce production cost. The report explains some basic concept of reliability analysis method, random variables in reliability design can be treated as a probability function. The probability distribution types are also introduced in the report. If the structures are relative simple, the numerical integration can be used to solve the probability of failure. However, the numerical integration is not suitable to analysis the complex structures in engineering design. Hence, there are three types of methods will be introduced to calculate the probabilities of failure. i.e. the safety index method, the safety index method and the numerical method. This report introduces the structural reliability analysis method by using finite element analysis software, ANSYS and analysis two complex structures to evaluate the probabilities of failure. Finite element analysis is a numerical technique that can perform analysis in solid mechanics, heat transfer, fluid flow etc. For structural reliability-based design, finite element method is used for dividing the complex structures into many small finite elements and solving the unknown random variables with each element. Two models will be performed the probability analysis by using different sampling methods and the results of failure probabilities will be discussed in the report.